Analysis of Quality Attributes and Household Type Moderation on Attitudes and Intentions to Reuse Online Food Delivery Applications - Warnida, Ira Puspa; Astuti, Rifelly Dewi (Journal of Management and Business Review, 2025)
The rapid growth of online food delivery services in Indonesia, driven by the online-to-offline (O2O) business model, highlights the need to understand the factors influencing consumer behavior. This study explores how application-related attributes (e.g., design, trustworthiness, and personalization) and product-related factors (e.g., price, variety, reviews) affect consumers’ perceived value and their intention to continue using food delivery applications. Based on a modified research model from previous study, data was collected through Google Forms from 536 respondents, categorized into single-person and multi-person households. Structural Equation Modelling (SEM) with LISREL was employed to analyze the relationships between variables. The results revealed that design, trustworthiness, and personalization significantly positively influenced perceived value, while convenience, food variety, and reviews had a negative effect. Additionally, user-perceived value positively impacted attitudes and the intention to continue using the app. Moderation analysis indicated significant differences in the effect of attributes between single-person and multi-person households, emphasizing the importance of household composition in consumer behavior. These findings provide valuable insights for food delivery platforms to tailor their offerings and marketing strategies, improving user satisfaction and retention in a competitive market.